2014
DOI: 10.1039/c4ra01042f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition of diamond on an adamantane-coated sapphire substrate

Abstract: Continuous diamond thin films can be grown on sapphire substrates by microwave plasma chemical vapor deposition utilizing a pretreatment of adamantane dip coating on the substrate for enhanced nucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…In the case of 5 h growth, partial delamination of the diamond layer was observed from the surface during the cooling cycle at the end of the recipe. We believe this was caused by the large compressive stress in sapphire wafer during the cooling cycle, which was also reported by others [21,40]. This issue elaborated upon more in the next section.…”
Section: Grain Size and Thicknesssupporting
confidence: 77%
“…In the case of 5 h growth, partial delamination of the diamond layer was observed from the surface during the cooling cycle at the end of the recipe. We believe this was caused by the large compressive stress in sapphire wafer during the cooling cycle, which was also reported by others [21,40]. This issue elaborated upon more in the next section.…”
Section: Grain Size and Thicknesssupporting
confidence: 77%
“…176 If we compare the diamond growth by Chen et al 174,175 with that of Tiwari et al 173 discussed above, a marginal increase in seeding density can be seen. However, this can be attributed to the solvent 177 even though in the case of Chen et al 174,175 they do not see in any noticeable enhancement in seeding due to the solvents. In both the cases we see seeding density enhancement over spontaneous seeding but the enhancements are not enough to get pinhole free thin diamond lms.…”
Section: Chemical Nucleationmentioning
confidence: 84%
“…Similar results were obtained for diamond grown on sapphire. The authors had also reported a thick diamond lm grown on sapphire 175 (see Fig. 20a-c).…”
Section: Chemical Nucleationmentioning
confidence: 90%
See 1 more Smart Citation
“…Very recently, to further improve the surface covered by diamond seeds, adamantane (C 10 H 16 ) molecules i.e. subnanometer unit of diamond crystal [113] were deposited on sapphire substrates by dip-coating [114]. Diamond films were grown on these seeded substrates by microwave CVD plasma at 700°C.…”
Section: Deposition Of Ndsmentioning
confidence: 99%